Across-Species Transfer of Protection by Remote Ischemic Preconditioning With Species-Specific Myocardial Signal Transduction by Reperfusion Injury Salvage Kinase and Survival Activating Factor Enhancement Pathways. Issue 3 (17th July 2015) - Skyschally, Andreas; Gent, Sabine; Amanakis, Georgios; Schulte, Christiane; Kleinbongard, Petra; Heusch, Gerd
<x xml:space="preserve">Abstract</x> Rationale: Reduction of myocardial infarct size by remote ischemic preconditioning (RIPC), that is, cycles of ischemia/reperfusion in an organ remote from the heart before sustained myocardial ischemia/reperfusion, was confirmed in all species so far, including humans. Objective: To identify myocardial signal transduction of cardioprotection by RIPC. Methods and Results: Anesthetized pigs were subjected to RIPC (4×5/5 minutes hindlimb ischemia/reperfusion) or placebo (PLA) before 60/180 minutes coronary occlusion/reperfusion. Phosphorylation of protein kinase B, extracellular signal–regulated kinase 1/2 (reperfusion injury salvage kinase [RISK] pathway), and signal transducer and activator of transcription 3 (survival activating factor enhancement [SAFE] pathway) in the area at risk was determined by Western blot. Wortmannin/U0126 or AG490 was used for pharmacological RISK or SAFE blockade, respectively. Plasma sampled after RIPC or PLA, respectively, was transferred to isolated bioassay rat hearts subjected to 30/120 minutes global ischemia/reperfusion. RIPC reduced infarct size in pigs to 16±11% versus 43±11% in PLA (% area at risk; mean±SD; P<0.05). RIPC increased the phosphorylation of signal transducer and activator of transcription 3 at early reperfusion, and AG490 abolished the protection, whereas RISK blockade did not. Signal transducer and activator of transcription 5 phosphorylation was decreased at early reperfusion in both RIPC and PLA. In isolated rat hearts, pig plasma taken after RIPC reduced infarct size (25±5% of ventricular mass versus 38±5% in PLA; P<0.05) and activated both RISK and SAFE. RISK or SAFE blockade abrogated this protection. Conclusions: Cardioprotection by RIPC in pigs causally involves activation of signal transducer and activator of transcription 3 but not of RISK. Protection can be transferred with plasma from pigs to isolated rat hearts where activation of both RISK and SAFE is causally involved. The myocardial signal transduction of RIPC is the same as that of ischemic postconditioning.